Pengaruh Intensitas Aset Biologis, Pertumbuhan, Dan Konsentrasi Kepemilikan Terhadap Pengungkapan Aset Biologis - Lenny Febiola Pangestu; Shanti Shanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Agricultural companies play an important role in the Indonesian economy in utilizing agricultural land, which can be seen from the increase in data from the Department of Agriculture each year. Agricultural companies have assets in the form of animals or living plants that undergo biological transformation in their management activities. These assets in the form of animals and living plants are referred to as biological assets. Disclosure of information on biological assets has been regulated in PSAK 241 Agriculture, of course, has an impact on the presentation of financial statements of agricultural companies in Indonesia. This study aims to examine the effect of biological asset intensity, growth, and ownership concentration on biological asset disclosure. This study is a quantitative study with hypothesis testing. The type of data used is quantitative data in the form of financial statements of agricultural companies listed on the Indonesia Stock Exchange. The sample used in this study was 27 agricultural companies selected using purposive sampling techniques and data analysis techniques using multiple linear regression. The results of the study indicate that biological asset intensity, growth, and ownership concentration do not affect biological asset disclosure.